Different light intensity on Messastrum gracile growth under phototrophic cultivation in laboratory - Sipaúba-Tavares, Lúcia Helena [UNESP]; Costa, Jesaias Ismael da [UNESP]; Fenerick, Débora Cristina [UNESP] (Springer Nature, 2024)
The present research evaluates the effects of three different lighting intensities, 60 (control), 30 and 120 µmol photons m− 2 s− 1 on Messastrum gracile growth. The observations indicated that a light intensity of 60 µmol photons m− 2 s− 1 resulted in higher cell density during experimental period. The light intensity of 120 µmol photons m− 2 s− 1 had a strong negative impact on M. gracile growth. Parameters such as lipid and protein content, cell density, chlorophyll-a and biomass were lower compared to the other light intensities. On the 14th and 21st growth days, the biomass, lipid and protein content were higher at 60 µmol photons m− 2 s− 1 with 800 mg L− 1, 5.7% and 34.4% biomass dry weight, respectively. The study also highlighted the economic aspects of M. gracile cultivation. The light intensities 30 and 60 µmol photons m− 2 s− 1 were found to be more advantageous than 120 µmol photons m− 2 s− 1 in terms of biomass, unit cost, lipid and protein content. Based on these findings, it was concluded that the light intensities of 30 and 60 µmol photons m− 2 s− 1 are more viable for M. gracile cultivation in laboratory under conditions used.
Keywords: Biological development; Biomass; CHU12; Economic aspects; Lighting